Faktor-Faktor Yang Dipertimbangkan Wisatawan Domestik Menginap Di The Harmony Legian Hotel Bali - Suyoga, A.A.Ngr Yudi Darma (E-Jurnal Manajemen, 2015)
Purpose of scientific research work entitled factors considered domestic travelers staying at The Harmony Legian Hotel Bali is for determine the dominant factor affecting tourist. Research method were used to answer the issues raised in this research is the analysis of factor. Variables studied were 30 variables derived from Hawkins, et al. (2007)’s article. By using PCA method, 30 variables obtained to 7 factors considered domestic travelers staying at The Harmony Legian Hotel Bali and its able to explain all the variance in the data. The seven factor that is product, environment, promotion, perception, people, social, and private.
Keywords: Marketing Mix, Consumer Interest